Machine tool control circuit skill training equipment - CHEN SHUTAI; ZHANG JUNBIN; YU BAILIN; SU GUOSHENG; XIE LEPEI; ZHUANG YONGXIN; XIE YUDE (2024)
The utility model discloses a machine tool control circuit skill training device, comprising a substrate, a mounting plate arranged on the bottom layer of the substrate, and a plurality of training components capable of being freely combined, the substrate is provided with a fault simulation unit used for simulating faults, the plurality of training components are electrically connected with the fault simulation unit, and the fault simulation unit is electrically connected with the mounting plate. The practical training components are detachably connected with the mounting plate, and different practical training components are detachably mounted to form different combined models so as to achieve the purpose of simulating fault maintenance skill practical training. According to the utility model, the practical training components are detachably connected with the mounting plate, and different practical training components are detachably mounted to form different combined models, so that the purpose of simulati